Prevalence and factors associated with depression and anxiety among patients recovered from COVID-19: a cross-sectional study in a tertiary care hospital in Nepal - Biraj Man Karmacharya; Kamal Gautam; Kalpana Chaudhary; Prasanna Rai; Shalik Ram Dhital; Shrinkhala Shrestha; Bandana Paneru; Akina Shrestha (BMJ Publishing Group, 2024)
Introduction COVID-19 has immensely affected the mental health of all people with prominent effects among the COVID-19 survivors who underwent hospitalisation. The evidence of the long-term mental health implications among the recovered COVID-19 patients remains unknown in Nepal. The study aimed to determine the prevalence of depression and anxiety and the associated factors among COVID-19 recovered patients.Methods An analytical cross-sectional study was conducted from May to August 2021 among 269 COVID-19 recovered patients admitted to Dhulikhel Hospital during the first wave (July 2020 to January 2021), and second wave (April 2021 to July 2021) of the COVID-19 pandemic. Anxiety and depression of the participants were assessed using the Hospital Anxiety and Depression Scale. Multivariate logistic regression analysis was performed to determine the factors associated with anxiety and depression.Results The prevalence of anxiety and depression were 38.66% (95% CI 32.99 to 44.65), and 30.48% (95% CI 25.24 to 36.28), respectively. Participants who received COVID-19 related information from the radio reported higher levels of anxiety and depression symptoms. Similarly, stigma, and being a health worker were significantly associated with a higher level of anxiety and depression symptoms, respectively. However, social support and long recovery duration were protective factors against anxiety and depression symptoms. Participants receiving a higher level of social support and having a recovery duration of 3-6 months, 7 months and more reported lower odds of anxiety and depression symptoms, respectively.Conclusions The greater prevalence of anxiety and depression symptoms among recovered COVID-19 patients highlights the need to design and implement appropriate mental health interventions. This could be done through psychosocial support and counselling services in health facilities, mental health service in emergency situation and post-discharge rehabilitation programmes.